Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
:Table of Content • Social Responsibility at King Saud University and Its Relationship with Academic Satisfaction from the Perspective of Graduate Students Mr. Ibrahim Nasser Saud Al-Maatash • The Educational Implications of Hadiths on the Chapter on Honoring Parents and Maintaining Kinship Relations from Riyad Al- Salihin book and Their Contemporary Applications Mr. Rafid Shalwan As- Salami • The Effectiveness of a Supervision Program in Developing the Counselling Supervision Skills of Student Guidance Female Supervisors at the Directorate General of Education in Makkah Province Dr. Amjad Ibrahim Al-Sharif, Dr. Hanan Abdulrahim Al-Malki • Redefining Educational Leadership in the Sultanate of Oman: From Standardization to Empowerment within a Paradigm Shift Mr. Saif Hamad Khamis Aljaradi, Prof. Rahmatoallh Marzooghi, Prof. Jafar Torkzadeh, Dr. Elham Heydari • The degree of use of the Artificial Intelligence Application (ChatGPT) by Arab Open University students in psychological counselling Dr. Moosa Sulaiman Al-Shuaili, Ms. Elham AbdulRahman Al-Riyami • Standardization of a scale for social competence of children aged 4–6 years; A field study in kindergartens in the interior regions of Israel Ms. Ehlas Ibrahem Nahle • The Formal Flaws of the Achievement Test Paper and Their Impact on Visual Processing Among General Education Students Mr. Ibrahim Abdullah Altoum